(untitled) (Geo-Eco-Marina, 2022)
Water consumption is rising due to global population growth, climate change, and other socioeconomic factors. The race to extract more water to meet the demands of various sectors is intensifying, making equitable water allocation challenging. An effort was made in this study to assess the water supply and demand gap among several sectors, namely energy, agriculture, and navigation in the lower Danube stretch, where water is shared by Serbia, Romania, and Bulgaria. The main study was conducted on water allocation needs for various sectors. To understand the water supply and demand balance under different conditions, three alternative scenarios were generated: dry, normal, and wet year periods. The Water Evaluation and Planning Model (WEAP) software tool was used to estimate the demand and supply gap in the research area for both energy production and irrigation, and a hydraulic model was used to determine the water depth corresponding to the flow remaining in the river after the withdrawals for energy and irrigation. The hydraulic model was based on the US Army core of Engineers tool HEC-RAS. In terms of water demand for energy production, the findings indicate that over a calendar year, the highest water demand is fulfilled during the month of April, while September has the lowest demand fulfilment. No water deficit has been found for agriculture water use in any of the defined scenarios, given the fact that available water in the system is much higher than the required crop water requirement (cwr) throughout the year. According to the hydraulic model results, water depth is rather low in dry years, which will have a detrimental impact on navigation.